The Right to Bequeath a Wife in a Polygamous Marriage According to The Compilation of Islamic Law - Nadya Farras Indriati; Febby Mutiara Nelson (IHSA Institute, 2022)
Marriage in Islamic law adheres to an open monogamy system, where a man is allowed to have more than one wife. Marriage has an influence on inheritance. The legal consequences that arise due to death are the emergence of rights and obligations. One of the inheritance problems occurs because of polygamous marriages. So the formulation of the problem in this paper regarding the rights of a wife and child from polygamous marriages according to the Compilation of Islamic Law in the case of the decision of the Religious Court Number: XX /Pdt.G/2013/PA.Bks. This research was conducted using a normative juridical research method with secondary data collection sourced from books related to the distribution of inheritance in polygamous marriages, as well as looking at the normative aspects in Law Number 1 of 1974, Compilation of Islamic Law, Decision of the Bekasi Religious Court No. XX /Pdt.G/2013/PA.Bks. Data analysis in this study was carried out qualitatively with deductive conclusions. The conclusion of this study is that it is possible for wives from polygamous marriages to jointly obtain property and inheritance from their husbands as regulated in Article 190 of the Compilation of Islamic Law and children from polygamous marriages are entitled to inherit property.